The Role of Psychology in Emergent Pediatric Limb Salvage and Reconstruction - Whitney M. Herge, PhD; Mikhail Samchukov, MD; Emily Elerson, RN; Alexander Cherkashin, MD; Elizabeth Hubbard, MD; David Podeszwa, MD (Elsevier, 2024)
Similar to elective pediatric limb lengthening and reconstruction (LLR) cases, treatment of pediatric patients undergoing emergent limb salvage and reconstruction (LSR) is approached as a multidisciplinary process. Unlike elective pediatric LLR, however, where the patient's individual interest in and motivation for LLR drives treatment decisions, emergent LSR treatment must be approached differently. In particular, the timing of emergent LSR treatment is driven by the risks associated with the patient's medical diagnosis and the potential consequences of nonintervention. Multidisciplinary treatment shifts from optimizing the patient's preoperative physical and psychological health to triaging and stabilizing the patient's physical and psychological health concurrent with LSR treatment. Without the luxury of preoperative time, the team must instead focus on physical and psychological risk mitigation, as well as the implementation of trauma-informed care, as appropriate.This work reviews the application of pediatric LLR preparation principles to emergent LSR scenarios. Our team's established six-step preparation workflow is adapted such that the timing, location, and focus of each step are individualized to the LSR patient's care needs. The team psychologist plays a particularly important role in this process in educating the multidisciplinary care team regarding the patient's specific psychological trauma symptoms, as appropriate, as well as ensuring the medical team takes a trauma-informed approach in their treatment provision and planning. Key Concepts: (1) Pediatric patients undergoing emergent LSR rarely have time for preoperative treatment preparation and, instead, typically must be evaluated after the index surgery. (2) Rather than focusing on preoperative physical and psychological optimization, the multidisciplinary team focuses on physical and psychological triage and stabilization concurrent with LSR intervention. (3) Treatment should be provided through a trauma-informed lens in recognition of the enormous stress that emergent LSR treatment often places on pediatric patients and families.